Enhanced thermal and mechanical properties of aluminum nitride ceramics through controlled whisker alignment: A comparative study of unidirectional and bidirectional configurations - Seo, Yewon; Ahn, Byeongho; Jeong, Hyeondeok; Nahm, Sahn; Ryu, Sung-Soo (Elsevier, 2025)
This study investigates the effects of aluminum nitride (AlN) whisker alignment on the thermal and mechanical properties of AlN ceramics fabricated through tape casting. By systematically comparing unidirectional (UNI) and bidirectional (BI) whisker arrangements, we examine how alignment configurations influence microstructural development and resulting properties. Bidirectionally aligned specimens achieved the highest thermal conductivity (200 W m-1 K-1, 30% increase) through three-dimensional networks of AlN whiskers. In contrast, unidirectionally aligned specimens exhibited superior mechanical performance with a 35% increase in fracture toughness (4.9 MPam0.5) through multiple toughening mechanisms enabled by bundles of closely-spaced whiskers. The enhanced properties stem from controlled anisotropic shrinkage during sintering, which creates optimized whisker spacing and orientation. Detailed microstructural analysis reveals distinct toughening mechanisms including crack deflection, branching, and grain bridging in UNI specimens, while BI specimens benefit from interconnected thermal pathways. This study demonstrates that controlled whisker alignment offers an effective approach to tailoring the thermal and mechanical properties of AlN substrates.